Reliability and optimization of structural systems : proceedings of the 10th IFIP WG7.5 Working Conference on Reliability and Optimization of Structural Systems, Osaka, Japan, 25-27 March 2002 /: proceedings of the 10th IFIP WG7.5 Working Conference on Reliability and Optimization of Structural Systems, Osaka, Japan, 25-27 March 2002. (2018) - Unknown
No abstract available